2010
DOI: 10.5902/198050981755
|View full text |Cite
|
Sign up to set email alerts
|

Análise de agrupamento em remanescente de Floresta Ombrófila Mista.

Abstract: RESUMOEste estudo teve como objetivo analisar a fitossociologia de um remanescente de Floresta Ombrófila Mista. Para isso, foram utilizados seis conglomerados, cada um com 16 parcelas, onde os indivíduos arbóreos e arbustivos com circunferência à altura do peito (CAP) igual ou maior de 30 cm foram identificadas e medidas. As espécies foram classificadas em grupos ecológicos e, com base nos dados de densidade, foi realizada uma análise de agrupamento utilizando o método TWINSPAN (Two-way Indicator Species Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
1
8
0
10
Order By: Relevance
“…Based on the cophenetic correlations of hierarchical clustering methods presented (Table 1), the method of average linkage provided better grouping, as it presented the highest cophenetic correlation (0.89), which was expected because the method of average distances produced better partitions than the single linkage, complete linkage and Ward's methods. It has been observed that Ward's method (0.39) provided the worst group, as it presented the smallest cophenetic correlation, which is in agreement with Barroso and Artes (2003) and Araujo, Chamil, Lonhhil, Avila, & Brena (2010), who also found similar results with the same methods but different species. Comparing is hierarchical methods (Table 1).…”
Section: Actascientiarum Technologysupporting
confidence: 78%
“…Based on the cophenetic correlations of hierarchical clustering methods presented (Table 1), the method of average linkage provided better grouping, as it presented the highest cophenetic correlation (0.89), which was expected because the method of average distances produced better partitions than the single linkage, complete linkage and Ward's methods. It has been observed that Ward's method (0.39) provided the worst group, as it presented the smallest cophenetic correlation, which is in agreement with Barroso and Artes (2003) and Araujo, Chamil, Lonhhil, Avila, & Brena (2010), who also found similar results with the same methods but different species. Comparing is hierarchical methods (Table 1).…”
Section: Actascientiarum Technologysupporting
confidence: 78%
“…Therefore, species like A. angustifolia and P. lambertii, which are dominant trees in the studied area (Santana 2016), often emphasised among the species of the prominent importance value index in phytosociological studies conducted on MOF of the Southern and Southeastern regions (Geraldi et al 2005;Seger et al 2005;Ribeiro et al 2007;Araujo et al 2010;Silva et al 2012;Souza et al 2012), can possibly be a determinant for the occurrence of epiphytic species shared by areas with this physiognomy, regardless of geographic distance or environmental variables. Wilberger et al (2009) andFurtado &Menini Neto (2015a) evaluated the vascular epiphytes on A. angustifolia and P. lambertii, respectively, showing their importance as support for the epiphytic synusia.…”
Section: Samyra Gomes Furtado and Luiz Menini Netomentioning
confidence: 98%
“…Para a caracterização química e física do solo, foram coletadas três amostras simples de solo, na camada 0 a 20 cm, formando a amostra composta, em cada uma das 32 parcelas inventariadas. Foram realizadas análises químicas, conforme metodologia proposta por Tedesco et al (1995) (NAPPO et al, 2000;ARAUJO et al, 2010;SANTOS et al, 2012). Assim, os dados de entrada consistiram em uma matriz principal de densidade das espécies (indivíduos/parcela), com CAP ≥ 30 cm, composta por 32 parcelas (linhas) e 22 espécies (colunas), e uma matriz secundária com 32 parcelas (linhas) e 24 variáveis ambientais (colunas).…”
Section: Methodsunclassified